Utilization of restricted use antimicrobials in patients in the Edgardo Rebagliati Martins National Hospital, Peru - Olivari-Veramendi, Erika (2020)
It is a descriptive, observational, cross-sectional and retrospective study, prescription-indication type DUS, whose objective was to evaluate the use of restricted-use antimicrobials (ATMR) in patients admitted to the Edgardo Rebagliati Martins National Hospital (HNERM) in the services: Internal Medicine, ICU, ICU pediatrics and general pediatrics in 2017, by determining the prevalence of ATMR prescription, the average of ATMR prescribed and percentage of prescription in combination per patient, the percentage of prescription based on non-specific clinical or laboratory basis and microbiologically based, and ATMRs and diagnoses presented more frequently. For data collection, 2 cards were applied: ATMR-S (ATMR per service) and ATMR-P (ATMR per patient) to a total of 418 patients for 21 days considering 27 ATMR. A prevalence of ATMR prescription of 41% is reported; on average 2 ATMRs per patient were prescribed and 56% of them received combined therapy; 51% of the prescriptions were based on microbiological examinations and 49% based solely on non-specific clinical or laboratory examinations; the most frequent diagnosis was respiratory sespsis, presented in 34% of patients, followed by urinary tract infection (UTI) 14%; the most prescribed ATMRs were: Meropenem, vancomycin, ceftriaxone and imipenem + cilastatin with 21, 19, 13 and 12% respectively.